2013
DOI: 10.1016/j.biochi.2012.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination based on Gly and Arg/Ser at position 673 between dipeptidyl-peptidase (DPP) 7 and DPP11, widely distributed DPPs in pathogenic and environmental gram-negative bacteria

Abstract: Porphyromonas gingivalis, an asaccharolytic gram-negative rod-shaped bacterium, expresses the novel Asp/Glu-specific dipeptidyl-peptidase (DPP) 11 (Ohara-Nemoto, Y. et al., (2011) J. Biol. Chem. 286, 38115-38127), which has been categorized as a member of the S46/DPP7 family that is preferential for hydrophobic residues at the P1 position. From that finding, 129 gene products constituting five clusters from the phylum Bacteroidetes have been newly annotated to either DPP7 or DPP11, whereas the remaining 135 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(67 citation statements)
references
References 38 publications
7
59
0
Order By: Relevance
“…Together with the present and previous observations of PgDPP4, including the kinetic parameters of enzymatic reactions, optimal pH, inhibitor profiles, and substrate preference for Pro and less for Ala (15,18,31), our results led us to conclude that the enzymatic properties of bacterial DPP4 substantially resemble those of the human entity (28,38). In fact, the present findings revealed release of the N-terminal dipeptide from the incretin peptides GLP-1 and GIP by bacterial DPP4.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Together with the present and previous observations of PgDPP4, including the kinetic parameters of enzymatic reactions, optimal pH, inhibitor profiles, and substrate preference for Pro and less for Ala (15,18,31), our results led us to conclude that the enzymatic properties of bacterial DPP4 substantially resemble those of the human entity (28,38). In fact, the present findings revealed release of the N-terminal dipeptide from the incretin peptides GLP-1 and GIP by bacterial DPP4.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, molecular masses of recombinant and native forms of DPP4 were estimated as approximately 9% smaller than those of the deduced sequences. This difference was not fully explained by the deletion of their signal sequences; however, this difference seems to be an intrinsic property of bacterial DPPs migrating on SDS-PAGE, since reductions of apparent masses on SDS-PAGE have been commonly observed for P. gingivalis DPP5 (15%) (15), DPP7 (10%) (31), and DPP11 (8%) (14).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…DPP4, DPP7, and DPP11, have been identified, of which DPP4 is highly specific for Pro and less potently for Ala at the penultimate position from the N terminus (P1) (MEROPS classification: S9.013) (21), whereas DPP7 prefers aliphatic and aromatic residues (22). We recently reported that DPP7 also releases dipeptides with a non-hydrophobic P1 residue, if the N-terminal (P2) residue is hydrophobic (23). The third and novel enzyme DPP11 (S46.002) shares a 38.7% amino acid sequence identity with DPP7 (S46.001), and is specific for Asp and Glu (24).…”
mentioning
confidence: 99%